The Effects of Skilled People's EEG-Based Neurofeedback Training on Learning the Air Rifle Shooting Skill in Novices - Farzaneh Hatami; farshid tahmasbi; hedieh pasbani (University of Tehran, 2023)
Introduction: This study aimed to determine the effects of skilled people's EEG-Based neurofeedback training on learning of the rifle shooting skills in novices.Methods: This applied study was a semi-experimental research with a pretest-posttest control group design. Thirty novice athletes (mean age: 20±1.509 years) voluntarily participated in this study and were assigned into three homogenous groups including Beta/Theta Neurofeedback, Neurofeedback based on the brain pattern of skilled rifle shooters (decreasing the Theta activity in Fz and F4 area, and increasing the low and high Alpha at the P3 and P7 area, and Control groups according to pretest scores. The acquisition phase consisted of 6 sessions. The control group only did physical exercise during the sessions.  48 hours after the last acquisition session, a retention test was conducted followed by a transfer test by a non-dominant hand to grab the weapon.Results: The results showed that the group with neurofeedback based on the brain patterns of skilled rifle shooters was significantly better than the other two groups in all sessions. In the retention test the group with neurofeedback based on the brain patterns of skilled rifle shooters significantly performed better than the other two groups and the Beta/Theta Neurofeedback group had better performance compared with the Control group. In the transfer test, both neurofeedback groups performed better than the Control group, but there was no significant difference between the two neurofeedback groups.Conclusion: Future research can accelerate the progress and reach the peak shooting performance for novices by correcting neurofeedback protocols according to the brain and the expertise relationship.